The Model of Pastoral Ministry for Priests in the Light of the Document Evangelii Gaudium - Vinsensius Hulu (Jurnal Iman dan Spiritualitas, 2026)
In the document Evangelii Gaudium, Pope Francis emphasises that the Church today faces serious challenges from secular culture, including consumerism, materialism, and individualism. These cultural dynamics pose significant obstacles to the realisation of authentic pastoral ministry. This article focuses on the ministry of priests within this context, particularly in urban settings in Indonesia, where such challenges are increasingly evident. In practice, some priests are confronted with temptations influenced by secular values, such as attachment to comfort zones, the pursuit of recognition, and a tendency toward a more luxurious, less missionary lifestyle. This study aims to propose a model of pastoral ministry, inspired by Evangelii Gaudium, that responds to contemporary challenges. Employing a qualitative approach through literature review and theological reflection, the study analyses key themes in the document in dialogue with biblical texts, especially the Gospels. The findings highlight three essential forms of pastoral ministry: a ministry that goes beyond the comfort zone, a compassionate ministry rooted in mercy, and a dialogical ministry grounded in listening and participation. These models are expected to provide a relevant, contextual framework for priests to carry out their mission more authentically and effectively. Ultimately, this study contributes to the renewal of pastoral ministry by integrating theological foundations with the concrete realities faced by priests in today’s world.